Biological and functional properties of human umbilical cord-derived lyophilized tissue-engineered matrices - A. A. Kondratenko; L. I. Kalyuzhnaya; D. V. Tovpeko; V. S. Sheveleva; R. I. Glushakov (Вестник трансплантологии и искусственных органов, 2023)
The use of tissue-engineered products (TEP) from decellularized extracellular matrix (dECM) to treat deep skin lesions is a tissue engineering method that promotes regenerative healing. Cell-free preparations reproduce the hierarchical complexity of tissues, mimic structural, biochemical and mechanical signals that are necessary to attract cells, and are a source of bioactive molecules. The human umbilical cord biomaterial has a fetal phenotype with extra-embryonic origin, and therefore is available and has no ethical limitations in its use. The tissue engineering laboratory at Kirov Military Medical Academy developed and patented a TEP from the highly regenerative human umbilical cord in the form of matrix and hydrogel matrix. To study its regenerative potential, lyophilisates of tissue-engineered solid-state and hydrogel matrices were implanted around mini pig fullthickness wounds in vivo. The external signs of inflammatory response and the histological images of biopsy specimens from the lyophilizate implantation areas were analyzed. The effect of nutrient media, «conditioned» with lyophilizates of both matrices, on the viability and migration activity of fibroblast-like cells, isolated from mini pig skin, was investigated. The matrix lyophilisates showed good biocompatibility and bioactivity in in vitro and in vivo experiments. Implantation of the samples promoted faster formation of mature epidermis compared to the control.